ON THE ASSESSMENT OF STUDENTS’ KNOWLEDGE IN THE LESSONS OF STRUCTURAL MECHANICS - Daminov Jakbarali Abduvalievich; Mahmudov Zokirjon Sotivoldievich; Rakhimov Abdulvoris Mutalovich; Najmiddinov Insomiddin Biloldinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The possibility of using the confusing logic chain method in the science of structural mechanics is detailed in a number of examples.